The COVID-19 and online education during emergencies in higher education: A case study of Islamic University in Uganda Females Campus (IUIUFC). - Nabukeera, Madinah (Archives of Business Research, 2020)
Higher education faced unplanned, unwanted, un experienced, tense test in online learning with Novel Covid-19 pandemic. For all the stakeholders participating in this type of training from lecturers, students and support ICT staff its unwelcome but the university systems were stuck on how they have to go through to ensure that they end Semester II academic year 2019/20. Early January 2020, the outbreak of the Covid-19 caused Ugandan universities to close the physical campuses following a presidential directive. On 20th March 2020, from lower primary, secondary education to universities. This forced university administration to instruct teaching staff to teach all courses on-line apart from practical courses that need laboratory training. This paper focused on instructional strategies in Uganda and focuses on a case of Islamic University in Uganda Females’ Campus (IUIUFC). Fifteen specific instructional strategies are presented to summarize current online teaching experiences for university instructors who might conduct online education in similar circumstances. The study concluded with 15 high impact principles for online education. Keywords: Covid-19, instructional strategies, online teach and learning, academic managers and IUIUFC